An Instruments Developing Cashless in Malaysia - Taasim, Shairil Izwan; Yusoff, Remali (Shirkah: Journal of Economics and Business, 2017)
This study aims to apply the technology assessment (TA) model on e-banking perceptions in the context of Malaysia, which involves aspects of supply and demand, and increasing the cashless concept in the country. A sample of 470 respondents were randomly selected from high density state capitals and major cities, through the convenience sampling method. Respondents were requested to complete a questionnaire developed from the basic model by forming UTAUT constructs, including quality, skills, transaction costs, user satisfaction, role of service providers (banks), and the influence of environment. Based on the results obtained, the model suggests that transaction costs, as direct costs by service providers, have a significant impact on the overall assessment of the performance of retail e-banking. Data analysis was performed using structured equation modeling (SEM), with the use of AMOS V22 as a method of trajectory analysis. Keywords: technology, SEM, performance, e-banking